Peran Panitia Pemungutan Suara (PPS) dan Tokoh Masyarakatdalam Melakukan Sosialisasi untuk Meningkatkan PartisipasiMasyarakat pada Pemilihan Kepala Daerah Tahun 2015(Studi Kasus Kelurahan Giriwono Kecamatan Wonogiri Kabupaten Wonogiri) - Utami, Afrina Wahyu; , Dr. Ahmad Muhibbin, M.Si (2016)
The purpose of this study are: 1. Knowing the role of the committee voting (PPS)and community leaders in socializing at the local elections in 2015 Giriwono administrative districts of Wonogiri Wonogiri district, 2. Knowing the role of the committee voting (PPS) dann community leaders to promote public participation in local elections in 2015 Giriwono administrative districts of Wonogiri Wonogiri district, 3. Knowing how much the level of community participation in local elections in 2015 Giriwono administrative districts Wonogiri Wonogiri district. This study uses data source from an informant or informants, events and documentation. Type a descriptive qualitative research. The technique of collecting data using nterviews, observation and reviewing documents or records. To test the validity of the data using the credibility of data including prolonged observation and triangulation, ie triangulation triangulation of data sources and data collection techniques. His analysis using interactive analysis that is used to describe the data obtained through interviews, observation and documentation review. Results of the study are: 1. The role of the committee voting (PPS) and community leaders in socializing at the local elections in 2015, followed by the general public, in which there are elements of first-time voters, and community Karangtaruna umum. Material presented in socialization includes Tahaan election nomination from stage to stage recapitulation of the election results, 2. The role of the committee voting (PPS) and community leaders to increase participation is to conduct intensive socialization of the village community Giriwono, 3. The level of participation in local elections in 2015 has increased significantly compared with the regional head election in 2010 that is equal to 7.09%. Which semulan only 60% to 67.09%.